Selective Catalytic Oxidation of Alcohols, Aldehydes, Alkanes and Alkenes Employing Manganese Catalysts and Hydrogen Peroxide. Issue 13 (9th September 2013) - Saisaha, Pattama; Buettner, Lea; van der Meer, Margarethe; Hage, Ronald; Feringa, Ben L.; Browne, Wesley R.; de Boer, Johannes W.
Abstract The manganese‐containing catalytic system [MnIV, IV2O3(tmtacn)2]2+ (1)/carboxylic acid (where tmtacn=N, N′, N′′‐trimethyl‐1, 4, 7‐triazacyclononane), initially identified for the cis‐dihydroxylation and epoxidation of alkenes, is applied for a wide range of oxidative transformations, including oxidation of alkanes, alcohols and aldehydes employing H2O2 as oxidant. The substrate classes examined include primary and secondary aliphatic and aromatic alcohols, aldehydes, and alkenes. The emphasis is not primarily on identifying optimum conditions for each individual substrate, but understanding the various factors that affect the reactivity of the Mn‐tmtacn catalytic system and to explore which functional groups are oxidised preferentially. This catalytic system, of which the reactivity can be tuned by variation of the carboxylato ligands of the in situ formed [MnIII, III2(O)(RCO2)2(tmtacn)2]2+ dimers, employs H2O2 in a highly atom efficient manner. In addition, several substrates containing more than one oxidation sensitive group could be oxidised selectively, in certain cases even in the absence of protecting groups. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>